2018
DOI: 10.1155/2018/7390618
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Biodegradation of Mesoporous Silica Nanoparticles by Means of Experimental Parameters and Surface Functionalization

Abstract: Mesoporous silica nanoparticles (MSNPs) are gaining a large interest in the field of medical and biomedical applications due to their biodegradability and high loading capacity as a carrier. In this work, a simple synthesis and functionalization procedure is reported, which allows tuning the nanoparticle properties, functionalization, and biodegradability. Variations in the synthesis procedure are introduced, including temperature, concentration of catalyst, and surface functionalization. These samples are cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…The hydrodynamic size of the nanoparticles obtained by DLS, as expected, shows a significant overestimation of their size when compared to TEM measurements, owing mainly to the influence of surface coating and hydration layer on the diffusion of the nanoparticles. 49,50 In the FT-IR spectra ( Figure S2) it is possible to observe the main bands related to the Si-O symmetrical (812 cm −1 ) and asymmetrical (1092 cm −1 ) stretching. 51 With the addition of amine-containing silane (red) new bands arise, such as C-N stretching (1232 cm −1 ) and N-H bending (1403 cm −1 ) of primary amines, N-H stretching (3671 cm −1 ) of secondary amines or amide and alkane stretching bands (2979, 2902 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hydrodynamic size of the nanoparticles obtained by DLS, as expected, shows a significant overestimation of their size when compared to TEM measurements, owing mainly to the influence of surface coating and hydration layer on the diffusion of the nanoparticles. 49,50 In the FT-IR spectra ( Figure S2) it is possible to observe the main bands related to the Si-O symmetrical (812 cm −1 ) and asymmetrical (1092 cm −1 ) stretching. 51 With the addition of amine-containing silane (red) new bands arise, such as C-N stretching (1232 cm −1 ) and N-H bending (1403 cm −1 ) of primary amines, N-H stretching (3671 cm −1 ) of secondary amines or amide and alkane stretching bands (2979, 2902 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…They showed that degradation of MSNs increases with high concentration of MSNs, and low amount of catalyst and low temperatures used for the synthesis of MSNs. They also showed that amino group surface functionalization increased the degradation rate compared to the carboxylated and nonfunctionalized MSNs . In 2019, Zhang et al constructed organic‐inorganic hybrid MSNs loaded with doxorubicin and siRNA as a nanocarrier platform for synergistic anticancer therapies.…”
Section: Elimination Of Degradable Msnsmentioning
confidence: 99%
“…This work is a refinement of our previously reported MSNP synthesis procedure (Seré et al, 2018). Therefore, the influence of different silica precursors and dialysis alcohols was assessed, and NPs with different functional groups were produced as a reference for characterization.…”
Section: Msnp Synthesis and Characterizationmentioning
confidence: 98%
“…Silica is already an additive in medical formulations. In addition, these particles offer biocompatibility and biodegradability, relatively high chemical and mechanical stability, a variety of surface functionalization due to abundant silanol groups and a simple synthesis procedure which can easily be upscaled to industrial applications (Seré et al, 2018).…”
Section: Introductionmentioning
confidence: 99%